Synthesis of Nanoplatelet Zinc Borate and its Combination with Expandable Graphite and Red Phosphorus as Flame Retardants for Polypropylene - Doanh, Truong Cong; Nhung, Hac Thi; Hanh, Nguyen Thi; Hien, Nguyen Thi Thu; Dat, Doan Tien; Tan, Vu Minh; Ha, Hoang Mai (VNU Journal of Science: Natural Sciences and Technology, 2022)
The zinc borate nanoparticles (2ZnO.3B 2 O 3 .3H 2 O) were successfully prepared by precipitation reaction in aqueous solutions of borax and zinc sulfate using oleic acid as a surfactant. The structural, morphological characteristics and the wettability of the particle surface were studied through Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and the contact angle. The hydrophobic zinc borate (n-ZB) had nanoplatelet morphology with a diameter of 1.0 - 1.5 µm and thickness of about 90 nm. Nano zinc borate showed a synergistic influence with expandable graphite (EG) and red phosphorus (RP) on the flame retardant properties and thermo-oxidative stability of polypropylene (PP). The nanocomposite 7n-ZB/7RP/7EG/PP achieved the V-1 UL94 verticle burning test with a limited oxygen index of 23.7% and the char yield of 14.67 wt.% at 900 o C. Furthermore, the fire retardant performance and the mechanical properties of the nanocomposites loading ZB nanoparticles were improved compared with the composites employing commercial ZB microparticles.